Viscous Hydrodynamic Model for Relativistic Heavy Ion Collisions - A. K. Chaudhuri (Advances in High Energy Physics)
Viscous hydrodynamical modeling of relativistic heavy ion collisions has been highly successful in explaining bulk of the experimental data in RHIC and LHC energy collisions. We briefly review viscous hydrodynamics modeling of high energy nuclear collisions. Basic ingredients of the modeling, the hydrodynamic equations, relaxation equations for dissipative forces, are discussed. Hydrodynamical modeling being a boundary value problem, we discuss the initial conditions, freeze-out process. We also show representative simulation results in comparison with experimental data. We also discuss the recent developments in event-by-event hydrodynamics.